Una lectura hipermoderna de La risa de Henri Bergson. De la risa como pequeño enigma malicioso a su comprensión como ethos de las sociedades - Solís Castro, Salvador (2019)
“A Hypermodern Reading of Laughter by Henri Bergson. From Laughter as a Malicious Little Enigma to its Understanding as an ethos of Societies”. In this essay, we analyze some important aspects of the interpretation elaborated by Henri Bergson regarding “laughter” and the phenomenon of the comical, especially in its relation to the social. This aspect, crucial in our opinion, is what allows us to think about this phenomenon beyond the pure aesthetic frontier, and towards the always-difficult boundaries of the ethos. Also taking into account the connection between this proposal and other aspects of the so-called “bergsonism”, in what follows we affirm and defend the corrective and ethical potential of laughter within the generality of its philosophy.